DI BALIK LAYAR MEDIA SOSIAL: BAGAIMANA DOXING MENJADI ALAT MEMBUNGKAM AKTIVIS, MEMBUNGKAM KRITIS, DAN MERUSAK KEBEBASAN DIGITAL - Fitri Sri Armaini; Widya Oktaviani; Cicilia Audri Ardianti; Syahla Aulia Faradila; Deyna Ayustiatmojo (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study examines the practice of doxing in Indonesia which is used as an instrument to silence activists and undermine digital freedom, as well as analyze the legal response through Law Number 1 of 2024 concerning Information and Electronic Technology (ITE Law) and Law Number 27 of 2022 concerning Personal Data Protection (PDP Law). Doxing, which is the unauthorized publication of personal data for intimidation purposes, has created a serious chilling effect for critical voices. The cases against activists show that this threat is real and requires effective legal action to maintain civil security. The results of the analysis show that although Law Number 1 of 2024 concerning Information and Electronic Technology (ITE Law) and Law Number 27 of 2022 concerning Personal Data Protection (PDP Law) have provided a legal basis, the regulation is inadequate because it does not specifically formulate doxing as a cybercrime, thus creating a legal loophole. The study concludes that this legal gap leads to ineffective law enforcement and inadequate protection for victims' rights to rehabilitation and compensation. Therefore, it is necessary to synchronize the law, improve the competence of the apparatus, and strengthen victim protection more comprehensively.